Risk perception and usage of non-occupational post-exposure prophylaxis among fisherfolk in Ggulwe parish on the shores of Lake Victoria in central Uganda - Daraus Bahikire; Miisa Nanyingi; Christine Atuhairwe; Catherine Matama; Lesley Rose Ninsiima; Mudarshiru Bbuye; Mudarshiru Bbuye (Frontiers in Public Health, 2023)
BackgroundThe use of non-occupational post-exposure prophylaxis (nPEP) to prevent HIV acquisition among those exposed as an approach to HIV prevention has expanded in Uganda. Although there are increased efforts to avail nPEP services among most at-risk populations, the usage of nPEP medicines remains low. Therefore, this study examined the risk perception and usage of non-occupational post-exposure prophylaxis (nPEP) among fisherfolk in the Ggulwe fishing parish, Bussi sub-county, Wakiso district.MethodsA cross-sectional study among adults was carried out from October 2020 to January 2021 in Ggulwe parish, Bussi sub-county, Wakiso district, to examine the usage of nPEP and factors influencing the usage. Data were collected using semi-structured questionnaires, and key informants' interviews were conducted among healthcare providers and the local leadership. The quantitative data were summarized using bivariate and multivariate logistic regression, while the qualitative data were analyzed thematically to enrich the quantitative results.ResultsOverall, 248 fisherfolk encountered an event that required the use of nPEP, and of these, 55/248 (22.2%) were able to use nPEP to prevent them from acquiring HIV. The usage of nPEP among adults in the Bussi sub-county, Wakiso district, was associated with not knowing that HIV can be prevented using nPEP medicines (AOR:0.1, 95% CI 0.03–0.36, p < 0.001), lack of knowledge of the existence of nPEP (AOR: 0.3, 95% CI 0.13–0.76, p = 0.01), the perception that nPEP can effectively prevent HIV infection after exposure (AOR 0.0586, 95% CI: 0.0177–0.1944, p < 0.001), and the community's opinion affecting the willingness to take nPEP (AOR 0.1924, 95% CI: 0.0380–0.9727, p = 0.0462).ConclusionThe usage of nPEP among fisherfolk was low (22.2%). The low usage of nPEP was associated with a lack of knowledge and awareness about nPEP. This effort to improve the usage of nPEP should include community sensitization and HIV infection prevention using nPEP to raise awareness about HIV infection exposures and the risk of HIV infection during non-occupational exposures.